1995
DOI: 10.1016/0167-4889(95)00075-4
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-induced programmed cell death in mouse thymocytes

Abstract: Exposure of mouse thymocytes to dopamine caused apoptosis (programmed cell death). This was manifested by cellular condensation and membrane damage shown by flow cytometry measurements and scanning electron microscopic study. Dopamine also affected thymocytic nuclei and their genomic DNA integrity. Most of the DNA molecules accumulated in a subdiploid peak in flow cytometry analysis, indicating DNA fragmentation to small particles. DNA analysis showed the typical pattern of 'DNA ladder' caused by internucleoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 20 publications
1
77
0
Order By: Relevance
“…What has separated sodium from potassium during apoptosis is the occurrence of an early increase in sodium during the cell death process. Several initial studies on ions and apoptosis have reported this early increase in intracellular sodium [85][86][87][88]. Additionally, we have shown that apoptotic cells have a significant increase in intracellular sodium that occurs prior to the dramatic loss of cell volume with a variety of apoptotic agents in Jurkat T-cells [89].…”
Section: Sodium As a Signal During Apoptosismentioning
confidence: 89%
“…What has separated sodium from potassium during apoptosis is the occurrence of an early increase in sodium during the cell death process. Several initial studies on ions and apoptosis have reported this early increase in intracellular sodium [85][86][87][88]. Additionally, we have shown that apoptotic cells have a significant increase in intracellular sodium that occurs prior to the dramatic loss of cell volume with a variety of apoptotic agents in Jurkat T-cells [89].…”
Section: Sodium As a Signal During Apoptosismentioning
confidence: 89%
“…Dopamine and other catecholamines in micromolar concentrations induce degeneration of cultured cortical cells (32). In addition, sympathetic neurons and thymocytes exposed to high concentrations of dopamine undergo apoptosis characterized by cell body shrinkage, nuclear chromatin condensation, and internucleosomal DNA fragmentation (29,36). Metabolism of dopamine by monoamine oxidase or nonenzymatic autooxidation results in production of hydrogen peroxide and then free radicals, suggesting that dopamine induces oxidative neuronal death (14,28).…”
Section: R 1997 Academic Pressmentioning
confidence: 99%
“…Also, Na + deprivation should lead to a reduction in the intracellular Na + concentration. However, a decrease in the cytosolic Na + level does not provide a necessary condition for apoptosis induction because an increase in the intracellular Na + concentration was found to be coupled to apoptosis in several cell types [15][16][17][18]. Thus it is highly possible that persistent cell shrinkage per se and/or some signal downstream to shrinkage may be a causative factor(s) for apoptosis induction in HeLa cells exposed to Na + -free solution.…”
Section: Reverse-mode Operation Of Nkcc and Ncx Is Involved In Apoptomentioning
confidence: 99%